1982
DOI: 10.1254/jjp.32.591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal sympathectomy on sodium and water excretion in stroke-prone spontaneously hypertensive rats.

Abstract: Abstract-In stroke-prone spontaneously hypertensive rats (SHRSP), urinary excretion of sodium and water and glomerular filtration rate (GFR) are markedly decreased by acute normalization of the renal perfusion pressure using an aortic clamping technique.To examine the mechanism for the decreased sodium and water excretion, SHRSP rats were subjected to bilateral renal denervation.Sodium and water excretion and GFR in SHRSP with aortic clamping were significantly restored by the renal dener vation. The restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A number of studies now support that notion that rather than a generalized increase in sympathetic drive it may be a selective increase in activity to the kidney that is critical. The onset of hypertension appears to be delayed or the magnitude of the arterial pressure elevation reduced by chronic renal denervation (52,53,70,91,92). This interruption of arterial pressure elevation occurs in renin-dependent, renin-independent, volume-expanded, and genetic models of hypertension in rats, rabbits, and dogs.…”
Section: Current Approaches For Examining the Relevance Of The Sympatmentioning
confidence: 99%
“…A number of studies now support that notion that rather than a generalized increase in sympathetic drive it may be a selective increase in activity to the kidney that is critical. The onset of hypertension appears to be delayed or the magnitude of the arterial pressure elevation reduced by chronic renal denervation (52,53,70,91,92). This interruption of arterial pressure elevation occurs in renin-dependent, renin-independent, volume-expanded, and genetic models of hypertension in rats, rabbits, and dogs.…”
Section: Current Approaches For Examining the Relevance Of The Sympatmentioning
confidence: 99%
“…In animal studies, removal of the renal sympathetic nerves has been shown to delay the onset or reduce the magnitude of hypertension. [10][11][12][13][14][15][16] Overall, these results have been interpreted to suggest that an integral relationship exists between functional sympathetic outflow to the kidneys and the chronic regulation of arterial pressure.…”
Section: Sympathetic Nerve Activity To the Kidney Is Increasedmentioning
confidence: 89%
“…Total noradrenaline spillover is increased by approximately 40% in essential hypertension, with half of this increase derived from increases to the heart and kidneys, suggesting selective overactivity in the sympathetic nerves to these organs. In animal studies, removal of the renal sympathetic nerves has been shown to delay the onset or reduce the magnitude of hypertension 10–16 . Overall, these results have been interpreted to suggest that an integral relationship exists between functional sympathetic outflow to the kidneys and the chronic regulation of arterial pressure.…”
Section: Sympathetic Nerve Activity To the Kidney Is Increasedmentioning
confidence: 98%
“…This approach has revealed a disproportionate increase in sympathetic activity to the heart and kidneys in hypertension, with half of the increase in noradrenaline being accounted for by increased SNA to the heart and the kidney [15,16•]. In animal studies, removal of the renal sympathetic nerves has been shown to delay the onset or reduce the magnitude of hypertension [17][18][19][20][21]. Overall, these results have been interpreted to suggest that an integral relationship exists between functional sympathetic outflow to the kidneys and the chronic regulation of arterial pressure.…”
Section: Sympathetic Activity To the Kidney Is Increased Selectivelymentioning
confidence: 99%